2017
DOI: 10.3390/met7020061
|View full text |Cite
|
Sign up to set email alerts
|

DFT Investigation of the Effects of Coexisting Cations and Complexing Reagents on Ni(II) Adsorption by a Polyvinylidene Fluoride-Type Chelating Membrane Bearing Poly(Amino Phosphonic Acid) Groups

Abstract: Abstract:A polyvinylidene fluoride (PVDF)-type chelating membrane bearing poly(amino phosphonic acid) groups, denoted as ethylenediamine tetra(methylene phosphonic acid) (EDTMPA)-tetrabutyl orthotitanate (TBOT)/PVDF, was employed to remove Ni(II) from the aqueous solution. The effects of coexisting Ca(II), Pb(II), citrate, nitrilotriacetic acid (NTA) and ethylenediaminetetraacetic acid (EDTA) on the Ni(II) adsorption by this chelating membrane were revealed using density functional theory (DFT) calculations. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…It can be seen from SI Figure S2a that both samples present type IV isotherm curves. In addition, the BET surface area of PAMGO-3 (376.49 m 2 /g) is higher than that of MGO (129.37 m 2 /g) due to the introduction of PAPA onto the surface of PAMGO-3, this similar phenomenon was also reported by Liu et al 38 The pore size distributions of the two samples are shown in SI Figure S2b. According to the Barret-Joyner-Halenda (BJH) analysis, the average pore diameter and cumulative pore volume of PAMGO-3 are 5.4 nm and 0.31 cm 3 /g, respectively, much higher than those of MGO of 2.7 nm and 0.23 cm 3 /g.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…It can be seen from SI Figure S2a that both samples present type IV isotherm curves. In addition, the BET surface area of PAMGO-3 (376.49 m 2 /g) is higher than that of MGO (129.37 m 2 /g) due to the introduction of PAPA onto the surface of PAMGO-3, this similar phenomenon was also reported by Liu et al 38 The pore size distributions of the two samples are shown in SI Figure S2b. According to the Barret-Joyner-Halenda (BJH) analysis, the average pore diameter and cumulative pore volume of PAMGO-3 are 5.4 nm and 0.31 cm 3 /g, respectively, much higher than those of MGO of 2.7 nm and 0.23 cm 3 /g.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…This behavior was observed for each CYP450 (1A2 and 3A4), demonstrating that electron transference is taking place. This level of interaction between amino acids and ligands could be related to the charge transfer values, which means that the higher the ΔN values, the higher the interaction between compounds [34,35]. As was expected, the HEM group was responsible for the main interaction in the active site, with ΔN values higher than 0.6.…”
Section: Chemical Reactivity and Charge Transfer Calculations (∆N) Fomentioning
confidence: 60%
“…The observed differences in the interactions between CYP450 and AF, using several approaches of molecular modeling, provide a better understanding of the AF-CYP450 complex. Techniques like molecular docking and quantum chemical methods [36] and multivalent/multitargeted systems [37] This level of interaction between amino acids and ligands could be related to the charge transfer values, which means that the higher the ∆N values, the higher the interaction between compounds [34,35]. As was expected, the HEM group was responsible for the main interaction in the active site, with ∆N values higher than 0.6.…”
Section: Chemical Reactivity and Charge Transfer Calculations (∆N) Fomentioning
confidence: 86%
“…Moreover, the energies of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and the band gaps (Δ E HL ) of TPP-Lys-NTA and TPP-CC-Lys-NTA were calculated and compared to the already-known values of [Ni­(II)­(H 2 O) 6 ] 2+ (Table ). Interestingly, TPP-CC-Lys-NTA possesses higher HOMO energy than TPP-Lys-NTA , thus leading to a smaller HOMO–LUMO gap between TPP-CC-Lys-NTA (HOMO) and [Ni­(II)­(H 2 O) 6 ] 2+ (LUMO). This finding suggests that Ni­(II) and TPP-CC-Lys-NTA ligand present the most noticeable electrophilic and nucleophilic characteristics, respectively.…”
Section: Resultsmentioning
confidence: 99%